Experimental determination of the convective heat transfer coefficient for a switchgear busbar system with a use of the data reconciliation method. (25th May 2018) - Ryfa, A.; Smolka, J.; Bulinski, Z.; Bedkowski, M.
Highlights: Data reconciliation method was applied for heat losses determination. Heat transfer coefficient was determined for low-voltage switchgear. New expression for heat transfer coefficient for typical busbar system was presented. Influence of current on the heat transfer coefficient was assessed. Abstract: The paper proposes new approach for the determination of the convective heat transfer coefficient for the typical busbar system located in the industrial low-voltage naturally air-cooled electrical switchgear. The correlations for this parameter that are available in the literature are applicable for simple shapes only. This means that they were not designed for the application of the busbar system. In this study, a determination of the convective heat transfer coefficient is mainly based on the experimental values of the busbar and ambient temperatures, and the heat transfer rate dissipated from busbars. The coefficients of the proposed expressions for a Nusselt number were determined in the least square sense from the convective heat transfer coefficients and the measured temperatures to the postulated model. The convective heat transfer coefficients were obtained using the data reconciliation method for two energy balance equations defined at different locations and for the power loss equation for the AC current flow of the considered switchgear. The developed correlations used different than typical fluid temperatures to express the convective heat transfer coefficient to make the approach more practical. The method has been applied for four power levels for both ventilated and hermetic switchgear configurations.